Banks, regions and development - Alessandrini, Pietro; Papi, Luca; Zazzaro, Alberto (PSL Quarterly Review, 2012)
From the 1980s onwards the banking sectors in all the industrialised countries have been experiencing intense restructuring, aggregation and consolidation, radically changing their ownership structures and geography. Whatever the reasons behind such restructuring processes, the globalisation of the credit markets, the consolidation of banking structures, the removal of barriers to the free location of banks and their penetration of peripheral markets pose two main questions. Will integration of the banking systems lead to a narrowing or a widening of the development gap between regions? What relations will there be between financial centres and the periphery, and how will financial labour be divided between national (international) banks and local (regional) banks? The aim of this paper is to address such questions in the light of recent developments in the theoretical and empirical literature on financial integration. JEL Codes: G21, R11, G28, G34